Attracting medical students and doctors into surgical training in the UK and Ireland. (July 2019) - Walker, N.R.; Deekonda, P.; Glasbey, J.C.; Rashid, S.; Gokani, V.J.; Humm, G.; Mohan, H.; Harries, R.L.; ,
Abstract: Aims: Core surgical training (CST) programmes in the UK have seen a significant reduction in competition ratios over the past five years. This study aimed to determine motivating factors and perceived barriers to pursuing a career in surgery amongst junior doctors in training and medical students attending an annual conference. Methods: A self-reported, electronic questionnaire was distributed to medical students, foundation year doctors, and doctors in postgraduate surgical training programmes (DIPST) who attended the Association of Surgeons in Training (ASiT) Conference in 2016. Respondents ranked factors attracting them to a career in surgery and factors that could improve perceptions of surgical careers. Chi-square test was used to test for differences between groups (a = 0.05, R Studio, V3.3.1). Results: Of 394 respondents (response rate = 50.9%), 44.9% were medical students or foundation doctors ('Pre-CST') and 55.1% were DIPST ('Peri/post-CST'). Practical application of skills (97.4%), enjoyment of the theatre environment (95.4%) and positive experiences in surgical firms (84.7%) were primary driving factors towards a surgical career. Availability of private practice (32.2%), and sustainability of consultant jobs (49.0%) had less influence. For 'Pre-CST' respondents, role models (82.8% pre-CST v 74.9% peri-post CST, p < 0.05) and defined career progression (67.2% pre-CST v 47.0% peri-post CST, p < 0.001) were particularly important. 91% of all respondents agreed that a better balance of training and service within worked hours would improve perceptions of surgery. Conclusion: Addressing the motivating factors and perceived barriers to surgical careers will help bolster recruitment of the future surgical workforce.